Global trends in distributed leadership and school quality management: Enhancing work ethos in international baccalaureate schools in Indonesia - Anjaya, Capri Arista Dewi Anjaya; Komariah, Aan; Sururi, Sururi; Kurniatun, Taufani Chusnul (Universitas Jambi, Indonesia, 2026)
This study examines how distributed leadership and school quality management influence the work ethic of leaders in Satuan Pendidikan Kerjasama (SPK) schools implementing international curricula in Indonesia. A mixed-methods approach was employed, combining survey data with qualitative insights from Focus Group Discussions (FGD), Fishbone Analysis, and Importance–Performance Mapping Analysis (IPMA). The findings reveal that leadership empowerment, cross-cultural collaboration, and transparent management practices are crucial to strengthening the work ethic. Key challenges include limited professional development opportunities and hierarchical communication structures. The study proposes the CAPRI model—comprising Competence, Appraisal, Procedure, Resources, and Internal School Culture—as an integrated framework to enhance leadership work ethic. This model provides practical guidance for improving school management and organizational culture. Future research should involve larger samples and explore additional variables to strengthen the generalizability of the findings.